COLOMBIAN WILD LACTIC ACID BACTERIA (LAB) SHOW GOOD PROPERTIES IN SOURDOUGH MANUFACTURE - Ángela M. LEÓN P. (Universidad de Antioquia, 2009)
Sourdough breads are food products produced by lactic acid fermentation, with different sensorial, physicochemical and rheological properties from not acidified bread, that offer a nutritional option for colombian consumers. The aim of this study is to evaluate the effect of two wild Colombian lactic acid bacteria strains, Lactobacillus sp. LBM9 and Lactobacillus brevis LBM13, combined with a commercial strain of Saccharomyces cerevisae on the final properties of the dough and bread. Two isolates are selected from a collection and their growth curve is built. Physicochemical (final volume, pH, titrable acidity, protein percentage) and rheological (texture) properties are determined. Significant differencees between control and treatments are determined at α= 0,05 using Statgraphics 5,0 software. Results show that the most fitted wild colombian LAB isolates for sourdough bread making are Lactobacillus sp. LBM9 and Lactobacillus brevis LBM13 which reduce pH and increase dough acidity, reduce protein content, improve the final loaf volume, and retard staling.